An on-demand and on-site shape-designable mineralized hydrogel with calcium supply and inflammatory warning properties for cranial repair applications. Issue 18 (14th April 2022) - Zhang, Xin; Wang, Cheng; Wu, Jiangjie; Zheng, Ben; Chen, Si; Ma, Meng; Shi, Yanqin; He, Huiwen; Wang, Xu
Abstract : A novel mineral hydrogel achieves on-demand & on-site injection in cranial repair surgical operations by dispersing mineral ions at high temperature and inducing crystal generation at lower temperature, achieving plasticity, excellent strength and bone induction properties. Abstract : Although more than 2.2 million cranial repair surgical operations are performed every year, orthopedic doctors still dream of excellent artificial repair materials with suitable strength, on-site and on-demand fast-shaping properties, and bone induction properties. However, fast-shaping and high-strength properties seem to contradict each other, and even mineralized hydrogels, which already have excellent strength and bone induction properties, are not ideal candidates, since they lack the plasticity needed for complex craniofacial surface use during the essential mechanism of the process of the cleavage of inorganic ions, nucleation, and growth. Here, we report a novel mineralized hydrogel based on dispersing mineral ions prior to use and then inducing inorganic formation by decreasing the temperature, which endows the hydrogels with the characteristics of precise customization at an appropriate degree of mineralization and simultaneously achieves suitable mechanical properties and sufficient calcium supply for bone regeneration. Additionally, the calcium ion content in the water of the matrix will change with the temperature, and, thus, the conductivity of the mineralized hydrogels will change accordingly. This implements the ability to warn of inflammation in a timely fashion in the form of a temperature sensor. Therefore, this temperature-responsive hydrogel effectively achieves the aim of versatile material design.